2017
DOI: 10.1186/s41155-017-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Mind-Wandering Test for Spanish adolescents

Abstract: Background: Working memory capacity and fluent intelligence influence cognitive capacity as a predictive value of success. In line with this, one matter appears, that of mind wandering, which partly explains the variability in the results obtained from the subjects who do these tests. A recently developed measure to evaluate this phenomenon is the Mind-Wandering Questionnaire (MWQ). Objective: The objective of this work was to translate into Spanish the MWQ for its use with adolescents and to validate it and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…The factorial structure of the MWQ was analyzed by a confirmatory factorial analysis. The results of the confirmatory factorial analysis indicated that the model is fitted to the data, which confirmed the one scale's dimensional structure and corresponded with both the initial questionnaire postulates (Mrazek et al, 2013) and the factorial structure seen in the original questionnaire version, as well as in the results of confirmatory factorial analysis of the questionnaire in Spanish, Chinese and Japanese (Luo et al, 2016;Kajimura & Nomura, 2016;Salavera et al, 2017). Our results point to the appropriateness of using the Croatian translation of MWQ with adolescents.…”
Section: Reliability and Factor Structure Of The Croatian Translationsupporting
confidence: 80%
See 2 more Smart Citations
“…The factorial structure of the MWQ was analyzed by a confirmatory factorial analysis. The results of the confirmatory factorial analysis indicated that the model is fitted to the data, which confirmed the one scale's dimensional structure and corresponded with both the initial questionnaire postulates (Mrazek et al, 2013) and the factorial structure seen in the original questionnaire version, as well as in the results of confirmatory factorial analysis of the questionnaire in Spanish, Chinese and Japanese (Luo et al, 2016;Kajimura & Nomura, 2016;Salavera et al, 2017). Our results point to the appropriateness of using the Croatian translation of MWQ with adolescents.…”
Section: Reliability and Factor Structure Of The Croatian Translationsupporting
confidence: 80%
“…Previously, the MWQ was translated and validated in Spain (Salavera et al, 2017), China (Luo et al, 2016) and Japan (Kajimura & Nomura, 2016) and a singlefactor solution was confirmed in these studies. As there is no Croatian scale for mindwandering, translation and validation of the MWQ into the Croatian will enable the study of this phenomenon in the Croatian students.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The average age of participants was 21.97 years, and their ages ranged from 18 to 35 years, with a standard deviation of 3.91. For the Mind-Wandering Questionnaire (MWQ) [32], the Spanish translation was used [33]. This is a 5-item self-report questionnaire used to measure mind-wandering-related features on a 6-point Likert scale that goes from 1 (almost never) to 6 (almost always).…”
Section: Participantsmentioning
confidence: 99%
“…Our previous experience in validating other instruments with adolescent populations (Salavera, Urcola-Pardo, Usán, & Jarie, 2017) led us to evaluate the usefulness of this scale in a population of this age group. The authors' permission was requested and obtained for this purpose.…”
Section: Research Questionsmentioning
confidence: 99%